Inclusive Education in Russia: Historical-Sociological Aspect - Paramonova, Vera Aleksandrovna; Belikova, Ekaterina O.; Glazkova, Nataliay G. (KnE Social Sciences, 2021)
This research analyzes social-historic reasons of inclusive education and its essence and significance; its methodological basis along with its reasons and tasks are getting revealed; humanistic essence of inclusive education’s conceptions along with pedagogical principles with their implementation possibilities, are getting substantiated. Since inclusion in common understanding is an acknowledgement of diversity in educational environment, one of its aspects became the subject of analysis — which is joint studying process of healthy students and students with limited health abilities (herein referred to LHA). Humanistic criterion of education environment is ability to provide personal development and social integration for a child. First of all — this is a transition to genuine interaction and communication among all children with no differences. For this purpose, different forms of collective activities are used in conditions of barrier-free environment, thus, children could learn standards of social behavior and gain experience of its reproduction in the process of interaction. Thus, the purpose of inclusive education turns out to be education for everyone, and following new humanistic approaches signal the transition from teaching children with LHA in special facilities, to integrated education. Analysis of normative law documents in aspect of requirements which regulate organizing of inclusive education for children with limited health abilities in the system of general education of Russian Federation was conducted in this article. Basing on analysis of documents’ content, there was made a conclusion about sufficiency of normative law basis of inclusive education being integrated and implemented into the system of general education; it is also noted that there is unsolved question of researching enforcement practice quality in part of providing special conditions to get general education by children with limited health abilities under conditions of inclusion. The actuality of matter chosen is explained by necessity to search new conceptual solutions and strategies, helping to harmonize human relationships in general with adaptation of people with special education needs. Keywords: education, inclusion, judiciary system, students with limited health abilities (disabled students), inclusive education environment